From Good Deeds to Great Bonds: The CSR Path to Engagement, Trust, and Loyalty - Tania Monica Potu; Hope Wilfred Banda (Journal of Management and Entrepreneurship Research, 2026)
Objective: This research explores the relationship between corporate social responsibility (CSR) and customer engagement and client loyalty for long-term outcomes, with brand trust as the mediating variable, using a mineral water company as the research context. Research Design & Methods: An explanatory quantitative design was employed, using a cross-sectional survey of consumers of a mineral water company in Jakarta who are conscious of the company’s CSR initiatives. Purposive sampling yielded 211 valid responses, which were analyzed using SmartPLS 4.0. Findings: CSR outcomes indicate that CSR increases customer involvement, boosting brand trust and significantly affecting customer loyalty. Customer engagement and client loyalty are positively connected, with brand trust as a mediating factor. Implications & Recommendations: The findings signify that CSR is positively correlated with customer engagement, thereby significantly enhancing brand trust and strengthening client loyalty. The mediation mechanism suggests that CSR influences loyalty indirectly through engagement and trust, positioning it as a pivot tool for brand differentiation rather than mere compliance. It is recommended that the mineral water company reinforce the emotional and relational dimensions of its CSR initiatives by integrating them with marketing communications, maintaining transparency, communicating sustainability progress, and fostering participatory consumer engagement to sustain long-term loyalty. Contribution & Value Added: This study advances the literature by offering a process-based explanation of how CSR shapes client loyalty through an integrated mediation framework and underlying psychological mechanisms, such as brand engagement and brand trust, particularly in an emerging mineral water market.